Associations between Temporal Eating Patterns, Chronotypes and Overweight/Obesity: A Cross-Sectional Study among College Students - OuYang, Tian; Yang, Yao; Deng, Yadan; Zhao, Haiyi; Shah, Tayyib; Zhang, Yong (British Journal of Healthcare and Medical Research, 2026)
Aim: This study aimed to investigate the associations between temporal eating patterns, chronotypes and overweight/obesity among college students. Methods: In this cross-sectional study, 1101 undergraduates completed a validated meal pattern questionnaire (MPQ) and body composition assessment. Based on the meal timing data, the latent class analysis (LCA) method was used to identify four different dietary patterns. Overweight and obesity are defined by body mass index (BMI). Associations between these patterns, chronotypes and overweight/obesity were analyzed using logistic regression, calculating odds ratios (ORs) and 95% confidence intervals (CIs). Results: The temporal eating patterns were significantly associated with chronotypes and overweight/obesity. Compared to the “Conventional” pattern, the “Later snack” pattern was significantly associated with higher odds of overweight/obesity, particularly pronounced in female students. Compared to the “Intermediate Type” chronotypes, the “Definite Morning Type” was negative associated with the “Early Dinner”, “Late Dinner”, and “Later Snack” patterns. Similar negative associations were also observed for the “Moderate Morning Type” chronotypes. Both “Moderate Evening Type” and “Definite Evening Type” chronotypes showed strong positive associations with the “Later Dinner” pattern. No significance observed between chronotypes and overweight/obesity. Conclusions: A temporal eating pattern characterized by irregular meal and later snack timing was associated with an increased risk of overweight/obesity in college students, especially among females. Promoting earlier snack and regular meal schedules may help mitigate overweight/obesity risk in this population.